2016
DOI: 10.4103/2231-0762.181190
|View full text |Cite
|
Sign up to set email alerts
|

Detection and management of a complex canal configuration in mesiobuccal root of maxillary first molar using three dimensional imaging

Abstract: This case report discusses the identification and management of complex canal configuration of 3-2-1 in the mesiobuccal (MB) root of the maxillary left first molar. Careful attention to details of the pulpal floor and applying the knowledge of the laws of orifice location along with deepening the subpulpal groove with ultrasonic tips helped in identifying the three MB canals. Manual scouting helped in understanding the anatomic configuration; the use of three-dimensional imaging technique and spiral computed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…[ 1 2 ] Studies have shown the occurrence of third mesiobuccal canal to be in between 1.3% and 0.1%. [ 3 4 ] However, Lee et al . [ 5 ] and Kim et al .…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 2 ] Studies have shown the occurrence of third mesiobuccal canal to be in between 1.3% and 0.1%. [ 3 4 ] However, Lee et al . [ 5 ] and Kim et al .…”
Section: Introductionmentioning
confidence: 99%